Characterizing the relationship between health utility and renal function after kidney transplantation in UK and US: a cross-sectional study - Neri Luca; McEwan Phil; Sennfält Karin; Baboolal Kesh (Health and Quality of Life Outcomes, 2012)
Abstract Background Chronic allograft nephropathy (CAN) occurs in a large share of transplant recipients and it is the leading cause of graft loss despite the introduction of new and effective immunosuppressants. The reduction in renal function secondary to immunologic and non-immunologic CAN leads to several complications, including anemia and calcium-phosphorus metabolism imbalance and may be associated to worsening Health-Related Quality of Life. We sought to evaluate the relationship between kidney function and Euro-Qol 5 Dimension Index (EQ-5Dindex) scores after kidney transplantation and evaluate whether cross-cultural differences exist between UK and US. Methods This study is a secondary analysis of existing data gathered from two cross-sectional studies. We enrolled 233 and 209 subjects aged 18–74 years who received a kidney transplant in US and UK respectively. For the present analysis we excluded recipients with multiple or multi-organ transplantation, creatinine kinase ≥200 U/L, acute renal failure, and without creatinine assessments in 3 months pre-enrollment leaving 281 subjects overall. The questionnaires were administered independently in the two centers. Both packets included the EQ-5Dindex and socio-demographic items. We augmented the analytical dataset with information abstracted from clinical charts and administrative records including selected comorbidities and biochemistry test results. We used ordinary least squares and quantile regression adjusted for socio-demographic and clinical characteristics to assess the association between EQ-5Dindex and severity of chronic kidney disease (CKD). Results CKD severity was negatively associated with EQ-5Dindex in both samples (UK: ρ= −0.20, p=0.02; US: ρ= −0.21, p=0.02). The mean adjusted disutility associated to CKD stage 5 compared to CKD stage 1–2 was Δ= −0.38 in the UK sample, Δ= −0.11 in the US sample and Δ= −0.22 in the whole sample. The adjusted median disutility associated to CKD stage 5 compared to CKD stage 1–2 for the whole sample was 0.18 (p<0.01, quantile regression). Center effect was not statistically significant. Conclusions Impaired renal function is associated with reduced health-related quality of life independent of possible confounders, center-effect and analytic framework.